Deficiency in nucleoside diphosphate kinase B leads to endothelial activation of the hexosamine biosynthesis pathway and cardiac dysfunction - Shao, Feng; Wieland, Johanna; Wang, Yixin; Keles, Merve; Meng, Zenghui; Lomada, Santosh K.; Qin, Miao; Leiss, Veronika; Martin Garrido, Abel; Fuhrmann, Manuela; Qiu, Yi; Trogisch, Felix; et al. (Cardiovascular diabetology, 2025)
Nucleoside diphosphate kinase B (NDPKB) deficiency in endothelial cells (ECs) promotes the activation of the hexosamine biosynthesis pathway (HBP), leading to vascular damage in the retina. The aim of this study was to investigate the consequences of NDPKB deficiency in the mouse heart. NDPKB deficient mice were used in the study. Echocardiography was employed to assess cardiac function in vivo. Characterization of contractility in hiPSC-derived cardiomyocytes (hiPSC-CMs) was measured with the IonOptix contractility system. Immunoblotting and immunofluorescence were carried out to analyze the expression and localization of proteins in cultured cells and left ventricles (LVs). NDPKB deficient mice displayed impaired glucose tolerance and increased heart weight compared to controls. Echocardiographic analysis revealed an increase in the diastolic diameter of the left ventricular posterior wall (LVPW), a decrease in the early diastolic mitral valve E and E′ wave, and in the ratios of E/A and E′/A′ in NDPKB deficient hearts, suggesting cardiac hypertrophy and diastolic dysfunction. In line with cardiac dysfunction, the phosphorylation of myocardial phospholamban (PLN) and the expression of sarcoplasmic/endoplasmic reticulum Ca2+-ATPase 2 (SERCA2) in the NDPKB deficient LVs were significantly reduced. Moreover, the accumulation of collagen, fibronectin as well as the upregulation of transforming growth factor β (TGF-β), were detected in NDPKB deficient LVs. In addition, activation of the HBP and its downstream O-GlcNAc cycle was observed in the LVs and cardiac ECs (CECs) isolated from the NDPKB−/− mice. Furthermore, a bipolar O-GlcNAc regulation was identified in CMs. O-GlcNAc was decreased in NDPKB-depleted CMs, while conditioned medium from NDPKB-depleted ECs significantly increased O-GlcNAc levels, along with contractile and relaxation dysfunction of the hiPSC-CMs, which was attenuated by inhibiting endothelial HBP activation. Deficiency in NDPKB leads to endothelial activation of the HBP and cardiac dysfunction. Our findings may highlight the crucial role of proper endothelial HBP in maintaining cardiovascular homeostasis.